Pest interceptions on imported fresh fruits into South Africa - Nnzeru, Livhuwani R.; Tshikhudo, Phumudzo P.; Mudereri, Bester T.; Moshobane, Moleseng C. (Cambridge University Press, 2022)
Global trade through imports and exports of commodities brings an excessive risk of accidental introduction of invasive alien species in many countries. South Africa imports a range of fresh fruits and other commodities to complement its local production. Despite the substantial impacts of these invasive alien species, relatively little is known about the pathways and origins by which these organisms arrive in South Africa. In this study, we analyzed the susceptibility of South Africa to introduced plant-feeding pests detected from imported consignments of fresh fruits into the country over 10 years between 2009 and 2018. The analysis was conducted from pest samples drawn from 19 ports of entry through archived records, audits, and physical identifcation. A total of 378 species of pests, were taxonomically identifed, quantifed, and categorized into four groups, viz. quarantine, non-quarantine, potential quarantine, and uncategorized pest. Of the total examined pests, species identifed as potential quarantine or quarantine was relatively low, however, their risk on introduction is deemed unacceptable. Although the quarantine pest proportion was relatively low, our investigation also demonstrated that most intercepted pests were among the non-quarantine pests (74%), while 11% were uncategorized pests whose ecological impacts are relatively unknown. Thus, there is an urgent need for the revision of the current phytosanitary policies and border controls to intensify reduction in the future introduced alien invasive species. Also, there is a need for the intensifcation of surveys, monitoring, and tracing of the potential hazards that are likely to be caused by these identifed pests on the South African agriculture industry, the environment, and biodiversity. Our study can be used as a base for the improvement of the already available phytosanitary policies and provides baseline information for future research of the observed species and their relative control mechanisms.